A Constructionist Approach to Illocution: The Case of Orders - Nuria del Campo Martínez; Francisco José Ruiz de Mendoza (Miscelánea: A Journal of English and American Studies, 2013)
The present contribution studies the semantic base of orders at level 3 of the Lexical Constructional Model (Ruiz de Mendoza & Mairal 2008; Mairal & Ruiz de Mendoza 2009). The pragmatic structure of level 3 illocutionary constructions arises from the interplay between construal operations and general social conventions captured by the Cost-Benefit Cognitive Model (Ruiz de Mendoza & Baicchi 2007; Baicchi & Ruiz de Mendoza 2010). We examine the rationales for a number of conventionalized formulas carrying order values and explore their realizational potential. We argue that the realization of orders is based upon grammatical mechanisms that exhibit instantiation potential for relevant parts of the semantic base of ordering.
Keywords: illocutionary meaning; illocutionary constructions; Lexical-Constructional Model; ordering; conventionalization; Cost-Benefit Cognitive Model